The Role of 5-HT3 Receptors in Drug Abuse and as a Target for Pharmacotherapy - Engleman, E. A.; Rodd, Z. A.; Bell, R. L.; Murphy, J. M. (CNS & Neurological Disorders - Drug Targets, 2008)
Alcohol and drug abuse continue to be a major public health problem in the United States and other industrialized nations. Extensive preclinical research indicates the mesolimbic dopamine (DA) pathway and associated regions mediate the rewarding and reinforcing effects of drugs of abuse and natural rewards, such as food and sex. The serotonergic (5-HT) system, in concert with others neurotransmitter systems, plays a key role in modulating neuronal systems within the mesolimbic pathway. A substantial portion of this modulation is mediated by activity at the 5-HT3 receptor. The 5- HT3 receptor is unique among the 5-HT receptors in that it directly gates an ion channel inducing rapid depolarization that, in turn, causes the release of neurotransmitters and/or peptides. Preclinical findings indicate that antagonism of the 5- HT3 receptor in the ventral tegmental area, nucleus accumbens or amygdala reduces alcohol self-administration and/or alcohol- associated effects. Less is known about the effects of 5-HT3 receptor activity on the self-administration of other drugs of abuse or their associated effects. Clinical findings parallel the preclinical findings such that antagonism of the 5- HT3 receptor reduces alcohol consumption and some of its subjective effects. This review provides an overview of the structure, function, and pharmacology of 5-HT3 receptors, the role of these receptors in regulating DA neurotransmission in mesolimbic brain areas, and discusses data from animal and human studies implicating 5-HT3 receptors as targets for the development of new pharmacological agents to treat addictions.
Keywords: addictions